Productivity and quality of sweet potato roots propagated by mini-cuttings with different trays and seedling ages - Cardoso, Antonio Ismael Inácio [UNESP]; Nasser, Maurício D; Nakada-freitas, Pâmela G [UNESP]; Vieites, Rogério L [UNESP]; Martins, Bruno Nm [UNESP]; Ramos, Juliana A [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Rós, Amarilis B (Associação Brasileira de Horticultura, 2021)
The use of mini-cuttings is an option for obtaining sweet potato propagules of excellent quality. The objective of this research was to evaluate the production and quality of sweet potato roots propagated by mini-cuttings in different types of trays and ages of seedlings. Six treatments, resulting from the factorial 2x3, were evaluated: two types of trays (162 and 200 cells, with 31 and 18 mL of substrate per cell, respectively) and three ages of seedlings (39, 46 and 53 days after placement of mini-cuttings in trays), in a randomized block design, with five replications. Seedlings characteristics, production and quality of roots were evaluated. Higher number and dry weight of leaves per seedling were observed in the tray with 162 cells than in trays with 200 cells. The younger seedlings (39 days) had a lower number of leaves, dry weight of leaves, stem, roots ant total (leaves + stem + roots) than seedlings of other ages. There was no difference in root production depending on the type of tray, regardless of the age of the seedlings. For the 162-cell tray, the age of the seedlings did not affect the production of roots. On the other hand, for the 200-cell tray, higher roots production was observed on seedlings 39 days age compared to seedlings with 53 days. No differences were observed among the roots of different treatments for titratable acidity, and levels of sucrose, reducing sugars ant total sugars. It is recommended to avoid old seedlings, that is, it is recommended to use seedlings with a maximum of 43 days after planting of mini-cuttings for trays with 200 cells, while for trays with 162 cells no difference in root production was observed with the different ages of the seedlings.

A utilização de mini estacas é uma excelente opção para a propagação de batata doce. Objetivou-se com esta pesquisa avaliar a produção e a qualidade de raízes de batata doce propagada por mini-estacas em diferentes tipos de bandejas e idades de mudas. Foram avaliados seis tratamentos, resultantes do fatorial 2x3, sendo dois tipos de bandejas (162 e 200 células, com 31 e 18 mL de substrato por célula, respectivamente) e três idades das mudas no dia do transplante (39, 46 e 53 dias após a colocação das mini estacas nas bandejas), no delineamento em blocos ao acaso, com cinco repetições. Foram avaliadas as características das mudas, a produção e a qualidade das raízes. Foram observados maior número e massa seca de folhas por muda na bandeja com 162 células em comparação à de 200 células. As mudas mais novas (39 dias) apresentaram menor número de folhas, massa seca de folhas, caule, raízes e total (folhas + caule + raízes) que as mudas das outras idades. Não se observou diferença de produção de raízes em função do tipo de bandeja, independentemente da idade das mudas. A idade das mudas não afetou a produção de raízes com o uso da bandeja com 162 células. Por outro lado, empregando a bandeja com 200 células, observou-se maior produção de raízes usando mudas com 39 dias em comparação às mudas com 53 dias. Não foram observadas diferenças entre as raízes dos diferentes tratamentos para a acidez titulável, teores de sacarose, açúcares redutores e açúcares totais. Recomenda-se evitar a utilização de mudas velhas, ou seja, utilizar mudas com no máximo 43 dias após o plantio em bandejas com 200 células, enquanto que para bandejas com 162 células não foi observada diferença na produção de raízes com as diferentes idades das mudas.
Produtividade e qualidade de raízes de batata-doce propagada por mini-estacas em diferentes bandejas e idades de mudas
Keywords: Ipomoea batatas; propagation; substrate; Ipomoea batatas; propagação; substrato